PENGARUH BENTUK DAN KONFIGURASI AGREGAT TERHADAP KUAT TEKAN MORTAR - Hutagalung, Martin; Setiawan, Yanuar; Lie, Han Ay; Sabdono, Parang (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
This study aimed to investigate the influence of the shape and position of aggregate to compressive strength of matrix. Research conducted so far to say that the aggregate does not really affect the compressive strength of concrete and the opinions of experts who say that the aggregate rounded shaped is the aggregate are best used in the mix concrete . Therefore, there was a suggestion in this study to examine how the aggregate effect of the concrete compressive strength if we use the aggregate shaped beam (angular). That question will be answered by laboratory testing and modeling and analysis using software (SAP 2000). To determine the effect used variations size of aggregate measuring 2 x 2 x 5 cm and 2.5 x 1.5 x 5 cm at the time of casting is also variation in the position to determine the aggregate effect on the compressive strength of matrix. Tests conducted with uniaxial loading (one-way) and use the data logger and LVDT (Linear Variable Displacement Transducer), to measure the displacement that occurs. Through this research is expected, in addition to knowing their effects on the compressive strength of concrete, can also determine its relation to the concrete cracking pattern of voltage obtained when testing and validated by using SAP 2000.